DIRECT DEPOSITION OF RODS POLYANILINE ON COUNTER ELECTRODE SURFACE OF DYE-SENSITIZED SOLAR CELL BY POLSED DIRECT CURRENT ELECTROPOLYMERIZATION METHODS - Lestari Khasannah, Wiji
The material that is generally used as a counter electrode component in !Jye Sensiti=ed Solar Cell ( DSSC') i s plat inum (Pt) but the price of this material is expensive beca use of its low abunda nce on earth especiall y in Indonesia. One alternative su bstitut e material for Pt i s pol ya niline (PAN!) conductive pol ymer wh i ch has good electrocatalytic propert i es. Polyanil ine synthesized using direct current pu l sed el ectropolymeri zation has a n advantage over polyaniline synthesi zed using ordinary chemical methods because of its rod morphology. This rod morphology produces a larger surface area with an open channel system that facilitates the transfer of charge at the P ANl I electrol yte interface, thi s condition is expected to increase electrocatalyt i c activit y. The difference in PAN! morphology from thi s synthesis i s influenced by the electrical factors used in the synthesi s process. In thi s stud y PANJ synt h esi s was carried out using the pul sed el ectropolymeri zat ion method with variati ons in the frequency, amplitude and percent of the load cycle (duty percent cycle) during the synthesis process. FTIR spectra show•ed that PAN! Emeraldine Salt (ES) formed in the electropol ymeri zation process was characterized by the presence of typical P ANI ES peaks in al l var iat ions at wave numbers 1562, 1 482, 1294, 1 240, I I 1 9, a nd 8 1 6 em•'. Similarl y, the Raman spectra indicate that the PANI ES formed in the el ectropol ymerization process is characteri zed by the presence of typical PAN I ES peaks in all variations on the Raman sh ift 1 580, 1459, 1375, 1342, 1217, 11 59, 835, 780, 746, 525, and 412 cm- 1 . The performance test results show a n increase in fi•equency will result in a decrease in the energy conversi on efficiency of DSSC withadecreaseasfollows: 190°o(l Hz); 130°o(JOHz); l .27° o( l 00Hz); l . l 8°o ( 1 kHz); and 1 . 07° o (1 0 kHz). This i s in accordance with the SEM results where the d i ameter of PANJ ES is enlarged , respectivel y 67, 80, 1 86, 220, and 370 nm \.\hich results in a smaller surface area The DSSC efficiency resu lts al so showed a t endency to decrease wit h increasin g amplitude used, respect i vel y 1.70% ( 1.84 Y); 1 .58o (2.00 V), 1 .36° o (2.16 Y), l.l4°o (2.40 Y), and 0.99°o (2.64 Y). This data corresponds to the SEM results which experienced the following in creases• I 1 6, 1 76, 3 15, 353, and 382 nm whi ch results in a smaller surface area. Lik ewise, the duty percent variat i on obtained a decrease in effi ci ency in a row: 2.40° o ( I 0° o), 1 .72% (20°o); 1 .75% (30%); 1 .26% (40%); a nd 1.1 7% (50%) along with the